2018
DOI: 10.1186/s10033-018-0207-8
|View full text |Cite
|
Sign up to set email alerts
|

On Modeling Drilling Load in Lunar Regolith Simulant

Abstract: Drilling and coring, as effective ways to obtain lunar regolith along the longitudinal direction, are widely applied in the lunar sampling field. Conventionally, modeling of drill-soil interaction was divided into soil cutting and screw conveyance processes, ignoring the differences in soil mechanical properties between them. To improve the modeling accuracy, a hypothesis that divides the drill-soil interaction into four parts: cuttings screw conveyance, cuttings extruding, cuttings bulldozing, and in situ sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The large deflection and post-failure issues cannot be handled by the FEM. Moreover, the FEM may suffer from mesh distortion and results in an inaccurate solution [46].…”
Section: Finite Element Methodsmentioning
confidence: 99%
“…The large deflection and post-failure issues cannot be handled by the FEM. Moreover, the FEM may suffer from mesh distortion and results in an inaccurate solution [46].…”
Section: Finite Element Methodsmentioning
confidence: 99%
“…For investigations on Earth, a single Earth sample should be large enough to acquire an averaged representative composition through grinding processes without any other interference. Nevertheless, due to the scarcity of lunar samples, only a small quantity of pieces or repeatable usable slices, even lunar regolith simulant, such as CUMT-1 (McKay et al 1994;Quan et al 2018;Li et al 2022), are permitted to be investigated. If the demands for such investigations cannot be fulfilled, petitioners can submit an application with detailed descriptions of special scientific demands, and a slightly larger slice of samples could be prepared for the investigator after acceptance by scientific peer review (Zeigler et al 2007;Zhang et al 2020).…”
Section: Principals For Distribution and Repeatable Usagementioning
confidence: 99%
“…Isaka et al 10 studied the rake-type earth auger and the cone-tip-type earth auger, and found that the cone-tip-type earth auger can reduce the conveying torque better than the rake-type earth auger. Quan et al 11 proposed an iterative numerical calculation method for predicting drilling loads based on drilling experiments.…”
Section: F I G U R Ementioning
confidence: 99%